Chinese artificial intelligence in Africa: Digital colonisation or liberalisation? - Tinarwo, Joseph; Babu, Suresh Chandra (University of the Witwatersrand, 2023)
In this era of globalisation and progressive digitalisation, artificial intelligence (AI) has become an integral part of our everyday lives. While AI technology is lauded for increasing economic growth and solving some of the intricate global development challenges, such as climate change as well as disease and natural disaster forecasting, it has become a threat to citizen freedom and democracy and there are concerns of data privacy and security. China is rapidly expanding its AI and has emerged as one of the leading nations in artificial intelligence, research and development, particularly in the global South. Africa is one of the continents that has become a destination of the fast-expanding Chinese AI, notwithstanding that its impacts remain unknown. This research primarily adopted a qualitative research approach to examine the impact of Chinese AI in Africa and identify opportunities for facilitating positive influence of Chinese AI and digital presence in Africa. The study found that the expansion of Chinese AI in the global South, using Zimbabwe and South Africa as case studies, has been associated with mixed results. Since its beginning in the late 1970s after the economic reform, the Chinese AI-led automation has resulted in improved productivity, particularly in agriculture, health, infrastructure and manufacturing industries. However, the Chinese AI has been associated with gross human rights violations and promotion of corrupt practices, such as patronage and rent-seeking behaviour. Additionally, Chinese AI is undermining the rule of law and the functionality and legitimacy of weaker state institutions and processes.